Compared Outcomes of ST-Segment–Elevation Myocardial Infarction Patients With Multivessel Disease Treated With Primary Percutaneous Coronary Intervention and Preserved Fractional Flow Reserve of Nonculprit Lesions Treated Conservatively and of Those With Low Fractional Flow Reserve Managed Invasively: Insights From the FLOWER-MI Trial. (November 2021) - Denormandie, Pierre; Simon, Tabassome; Cayla, Guillaume; Steg, Philippe Gabriel; Montalescot, Gilles; Durand-Zaleski, Isabelle; le Bras, Alicia; le Breton, Hervé; Valy, Yann; Schiele, François; Cuisset, Thomas; Vanzetto, Gérald; et al.
Abstract : Background: In patients with ST-segment–elevation myocardial infarction and multivessel disease, percutaneous coronary intervention (PCI) for nonculprit lesions guided by fractional flow reserve (FFR) is superior to treatment of the culprit lesion alone. Whether deferring nonculprit PCI is safe in this specific context is questionable. We aimed to assess clinical outcomes at 1 year in ST-segment–elevation myocardial infarction patients with multivessel coronary artery disease and an FFR-guided strategy for nonculprit lesions, according to whether or not ≥1 PCI was performed. Methods: Outcomes were analyzed in patients of the randomized FLOWER-MI (Flow Evaluation to Guide Revascularization in Multivessel ST-Elevation Myocardial Infarction) trial in whom, after successful primary PCI, nonculprit lesions were assessed using FFR. The primary outcome was a composite of all-cause death, nonfatal myocardial infarction, and unplanned hospitalization with urgent revascularization at 1 year. Results: Among 1171 patients enrolled in this study, 586 were assigned to the FFR-guided group: 388 (66%) of them had ≥1 PCI, and 198 (34%) had no PCI. Mean FFR before decision (ie, PCI or not) of nonculprit lesions was 0.75±0.10 and 0.88±0.06, respectively. During follow-up, a primary outcome event occurred in 16 of 388 patients (4.1%) in patients with PCI and in 16 of 198 patients (8.1%) in patients without PCI (adjusted hazard ratio, 0.42 [95% CI, 0.20–0.88]; P =0.02). Conclusions: In patients with ST-segment–elevation myocardial infarction undergoing complete revascularization guided by FFR measurement, those with ≥1 PCI had lower event rates at 1 year, compared with patients with deferred PCI, suggesting that deferring lesions judged relevant by visual estimation but with FFR >0.80 may not be optimal in this context. Future randomized studies are needed to confirm these data. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02943954. Abstract : Supplemental Digital Content is available in the text.